Effect of probiotic “Subalin” on the productive parameters of age-0+ sturgeon hybrid (Acipenseridae) — bester under conditions of thermal load - Yu. Onyshchuk; O. Tretiak; O. Kolos (Ribogospodarsʹka Nauka Ukraïni)
Purpose. To determine the effect of adding the probiotic “Subalin” to the diet under conditions of elevated water temperature on productive parameters of age-0+ bester.